Two is More Than One: How to Combine Brain Stimulation Rehabilitative Training for Functional Recovery? - Koganemaru, Satoko; Fukuyama, Hidenao; Mima, Tatsuya (Frontiers in Systems Neuroscience, 2015)
A number of studies have shown that non-invasive brain stimulation has an additional effect in combination with rehabilitative therapy to enhance functional recovery than either therapy alone. The combination enhances use-dependent plasticity induced by repetitive training. The neurophysiological mechanism of the effects of this combination is based on associative plasticity. However, these effects were not reported in all cases. We propose a list of possible strategies to achieve an effective association between rehabilitative training with brain stimulation for plasticity: 1. the control of temporal aspect between stimulation and task execution, 2. the use of a shaped task for the combination, 3. the appropriate stimulation of neuronal circuits where use-dependent plastic changes occur, and 4. phase synchronization between rhythmically patterned brain stimulation and task-related patterned activities of neurons. To better utilize brain stimulation in neuro-rehabilitation, it is important to develop more effective techniques to combine them.